Efficacy of third-line pemetrexed monotherapy versus pemetrexed combination with bevacizumab in patients with advanced EGFR mutation-positive lung adenocarcinoma - Zhou, Cheng-Zhi; Qin, Yin-Yin; Xie, Zhan-Hong; Zhang, Jie-Xia; Ou-Yang, Ming; Li, Shi-Yue; Chen, Rong-Chang (Chinese Journal of Cancer Research; Vol 26, No 6 (December 30, 2014): Chinese Journal of Cancer Research, 2014)
Objective: The purposes of this study were to observe the effects of different treatment strategies, including third-line pemetrexed alone versus its combination with bevacizumab, in patients with advanced epidermal growth factor receptor (EGFR) mutation-positive lung adenocarcinoma, and to analyze the effects of the different medication orders of first- and second-line drugs on third-line efficacy. Patients and methods: One hundred and sixteen cases of patients with EGFR-positive lung adenocarcinoma who had received third-line pemetrexed alone or in combination with bevacizumab between March 2010 and March 2014 at Guangzhou Institute of Respiratory Diseases, the First Affiliated Hospital of Guangzhou Medical University were analyzed retrospectively. Additionally, all the patients were treated with first-line gemcitabine and cisplatin (GP) chemotherapy and second-line EGFR tyrosine kinase inhibitor (TKI) or with first-line EGFR-TKI and second-line GP chemotherapy. Results: The median survival of 61 cases with third-line pemetrexed monotherapy was 36.22 months, the median survival time of 55 cases with third-line pemetrexed plus bevacizumab was 38.76 months, and there was a significant difference in survival time between the two groups (P=0.04). Subgroup analysis revealed that among the 55 cases with third-line bevacizumab plus pemetrexed treatment, the median survival of 29 patients with first-line GP and second-line EGFR-TKI was 42.80 months, while the median survival of 26 patients with first-line EGFR-TKI and second-line GP was only 34.46 months; additionally, there was a significant difference in the survival time between the two subgroups (P=0.001). Among 61 cases with third-line pemetrexed treatment, the median survival of 34 patients with first-line GP and second-line EGFR-TKI was 38.72 months, while the median survival of 27 patients with first-line EGFR-TKI and second-line GP was only 32.94 months; the survival time of the two subgroups was significantly different (P=0.001). Conclusions: Regardless of the order of the first- and second-line chemotherapy and TKI therapy, the pemetrexed plus bevacizumab regimen was superior to the pemetrexed monotherapy as the third-line therapy in patients with advanced EGFR-positive lung adenocarcinoma. However, this strategy is worth further investigation in prospective studies.